Nutritional and antioxidant components and antioxidant capacity in green morph Amaranthus leafy vegetable - Sarker, Umakanta (Sci Rep, 2020)
Amaranth has two morphological types described as red and green morphs. Previous studies have extensively characterised red morph amaranth regarding both morphological and chemical properties including antioxidant activity, antioxidant phytochemical profile, mineral content and proximate composition. However, there is scarce information concerning green morph amaranth. Hence, the present study evaluated 12 green morph genotypes for proximate composition, antioxidant activity, antioxidant pigments, minerals, and phytochemicals. Green morph amaranth was found to contain abundant carbohydrates, dietary fiber and protein. We found notable levels of inorganic minerals including potassium, calcium, magnesium, iron, manganese, copper and zinc. Antioxidant capacity quantified as free radical quenching capacity varied between 27 and 48 μg g(−1) Trolox equivalents. We additionally quantified antioxidants, including total phenolics, total flavonoid equivalents and vitamin C, as well as the antioxidant pigments carotenoids, chlorophylls and betalains. These data indicated that four green morph genotypes could be considered as enriched in their antioxidant profiles. Green morph amaranth could be a potential source of nutritional components and antioxidant phytochemicals in the human diet providing opportunities to address mineral nutrient deficiencies and provide an antioxidant rich food